Melanins Protect Sporothrix brasiliensis and Sporothrix schenckii from the Antifungal Effects of Terbinafine - Almeida-Paes, Rodrigo (PLoS One, 2016)
Terbinafine is a recommended therapeutic alternative for patients with sporotrichosis who cannot use itraconazole due to drug interactions or side effects. Melanins are involved in resistance to antifungal drugs and Sporothrix species produce three different types of melanin. Therefore, in this study we evaluated whether Sporothrix melanins impact the efficacy of antifungal drugs. Minimal inhibitory concentrations (MIC) and minimal fungicidal concentrations (MFC) of two Sporothrix brasiliensis and four Sporothrix schenckii strains grown in the presence of the melanin precursors L-DOPA and L-tyrosine were similar to the MIC determined by the CLSI standard protocol for S. schenckii susceptibility to amphotericin B, ketoconazole, itraconazole or terbinafine. When MICs were determined in the presence of inhibitors to three pathways of melanin synthesis, we observed, in four strains, an increase in terbinafine susceptibility in the presence of tricyclazole, a DHN-melanin inhibitor. In addition, one S. schenckii strain grown in the presence of L-DOPA had a higher MFC value when compared to the control. Growth curves in presence of 2×MIC concentrations of terbinafine showed that pyomelanin and, to a lesser extent, eumelanin were able to protect the fungi against the fungicidal effect of this antifungal drug. Our results suggest that melanin protects the major pathogenic species of the Sporothrix complex from the effects of terbinafine and that the development of new antifungal drugs targeting melanin synthesis may improve sporotrichosis therapies.